Transformation and Integration of Traditional Values of Tirakatan and Sedekahbumi in Enhancing Interreligious Harmony and Social Cohesion in Society - Nuriyanto, Lilam Kadarin (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
Cultural traditions hold a significant role in the lives of rural Javanese communities, serving as expressions of gratitude toward nature and ancestral heritage. These ritual practices are not only annual activities but also symbolize the community's adaptation to modernization, strengthening social ties and maintaining social cohesion. However, technological advancements and social changes pose a threat to traditional values, as seen in the modification of cultural practices to maintain relevance in the modern era. This article addresses two main questions: how these practices influence interreligious harmony and social cohesion, and the impact of technological developments on the implementation of local traditions. By employing a qualitative approach along with theories of social transformation and social cohesion, this study highlights the importance of adapting traditions to retain their relevance and cultural values. The findings reveal that cultural practices serve as a foundation for reinforcing social relationships and religious tolerance, emphasizing the need for multicultural education to foster a harmonious society. This study focuses on the transformation and adaptation of traditions that reflect local identity and social solidarity amidst modernization. In this context, the role of the younger generation in preserving traditions as cultural heritage that embodies spiritual and social values becomes crucial. These findings are expected to provide insights into the preservation of traditions in the ever-changing modern context.